Housing, Land, and Property Restitution Rights of Refugees and Displaced Persons : Laws, Cases, andMaterials - Leckie, Scott (Cambridge University Press, 2013)
This volume contains some 240 of the most important international, regional,andnational standards and judicial decisions recognising and addressing themanycomplexitiesassociatedwiththehousing, land,andproperty restitution rights of refugeesand displaced persons. Many additional laws, cases, and materials on these themes are also in place throughout the world, but the selection found here attempts to provide an accurate and reasonably detailed picture of the current state of affairs with respect to these rights set within their various normative contexts.